(untitled) (Sirte Journal of Medical Sciences, 2025)
Inguinal hernias are the most prevalent in females, according to several sources in the western medical literature, followed by femoral and peri-umbilical hernias. However, our data in Sirte show that peri-umbilical hernias are the most common among females, with inguinal and femoral hernias lagging far behind. As a result, our Sirte data analysis differs significantly from those seen in journals and western medical texts. The article takes a critical approach on the causes behind the difference and explores the relevant literature.